REGULATION OF THE LEGAL PRACTITIONERS’ FIDELITY FUND INVESTMENTS IN NAMIBIA - Awarab, Marvin (Obiter, 2024)
In the Namibian context, the Legal Practitioners’ Fidelity Fund is created by statute, and is administered by a board of control known as the Legal Practitioners’ Fidelity Fund Board of Control.1 In terms of the law, the Board of Control (the Board) has the mandate to invest moneys of the fund from time to time if, in the opinion of the Board, such funds are not immediately required for other purposes.2 Market failures are continuously experienced globally, and may lead to failed investments. This reality requires investors to take proper steps to ensure that their investments are sound. The soundness of an investment rests in the possibility of increasing investment returns and reducing possible risk of investment failure. The Legal Practitioners Act does not provide any steps to follow to guard against the failure of fidelity fund investments. The Act also fails to indicate the extent to which the Board or any other person may be held accountable for failed investments. The Rules of the Law Society of Namibia are equally silent on this matter. This article seeks to investigate the extent to which the Board may be held liable for any failed investments. The article also attempts to establish various steps that should be followed by the Board to prevent or avoid the failure of fidelity fund investments.